Agenda de pesquisa da universidade pública : foco nas demandas das comunidades locais - Oliveira, Gisele Rosa de (2016)
Brazil is a country with a wide range of socais problems that need to be resolved so that it can be considered a developed nation. In this sense many social problems could be studied by public research in order to mitigate social inequality. This research aims to identify and understand the obstacles and possibilities for the formation of the research agenda of the public university demands from the local community. The methodology was qualitative and exploratory, which is outlined in literature and literature. The literature encompassed thematic as science, technology and innovation policy (PCT&I); channels of communication between university and society; social technology; and territorial development. The result of the survey pointed out as an obstacle to the construction of the university agenda based on the demands of local communities PCT&I developed based on international models; political control centered in the hands of a few actors, especially scientists; research agenda aimed at an international science, business or particular demands; lack of communication channels and strategies and exchange of knowledge between universities and local communities; little research on the research agenda of Brazilian scientists. As possibilities the search result pointed adherence by the PCT&I concepts such as: social technology; regional development; solidarity economy; social technology park; sustainable development; and actions as public policy development: municipalities, states (master plan) and urban planning.